2022
DOI: 10.1136/bmjopen-2021-055248
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision-making in advanced kidney disease: a scoping review

Abstract: ObjectivesTo provide a comprehensive overview of interventions that support shared decision-making (SDM) for treatment modality decisions in advanced kidney disease (AKD). To provide summarised information on their content, use and reported results. To provide an overview of interventions currently under development or investigation.DesignThe JBI methodology for scoping reviews was followed. This review conforms to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 150 publications
0
13
0
Order By: Relevance
“…Although several studies have demonstrated the beneficial effects of PDAs (Stacey et al, 2017;Winterbottom et al, 2016), barriers to the integration of PDAs (Scalia et al, 2019). Indeed, a lack of PDA implementation has also been described by Engels et al (2022). Our study showed that 1 year after the publication of the Dutch tools, only 28% of the HCPs reported that patients used the Three Good Questions, while 31%-33% of HCPs used the 'Overviews of options', and only 51% used the Kidney Guide.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although several studies have demonstrated the beneficial effects of PDAs (Stacey et al, 2017;Winterbottom et al, 2016), barriers to the integration of PDAs (Scalia et al, 2019). Indeed, a lack of PDA implementation has also been described by Engels et al (2022). Our study showed that 1 year after the publication of the Dutch tools, only 28% of the HCPs reported that patients used the Three Good Questions, while 31%-33% of HCPs used the 'Overviews of options', and only 51% used the Kidney Guide.…”
Section: Discussionmentioning
confidence: 62%
“…However, many PDAs have been developed for patients with CKD. In 2020, Winterbottom et al conducted a review on PDAs specifically for patients with CKD, focusing on the choice between dialysis and conservative care (Winterbottom et al, 2020) (Engels et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Healthwise, 2022). A recent review of PtDAs in kidney disease and Google search did not identify any focusing on EoLC for people with kidney failure (Engels et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of these models, such as the Kidney Failure Risk Equation (KFRE), have been extensively validated and offer good predictive performance [ 9 11 , 37 41 ]. Even though well-validated models are readily available and guidelines recommend that nephrologists use CPMs, the actual use of CPMs in CKD practice seems limited [ 6 , 42 44 ]. This may be related to the CPMs themselves (e.g., limitations in predictive performance or user friendliness), and/or to the intended users (e.g., doubts about the reliability and generalizability of CPMs) [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the CPMs themselves (e.g., limitations in predictive performance or user friendliness), and/or to the intended users (e.g., doubts about the reliability and generalizability of CPMs) [ 43 , 44 ]. CPMs are also often developed without the input of end-users (i.e., patients and nephrologists), and as a consequence, lack clinical relevance [ 42 , 43 ]. In addition, patients and nephrologists often prioritize different (treatment) outcomes [ 45 , 46 ] and may have different needs and preferences regarding the use and purpose of CPMs in CKD practice.…”
Section: Introductionmentioning
confidence: 99%